Parametric study on optimum angle of V-shaped plate to mitigate blast load utilizing LS-DYNA - Mohd Zaid Othman; Mohd Rosdzimin Abdul Rahman; Mohd Rashdan Saad; Azam Che Idris; Khairul Hasni Kamarudin; Mohd Faizal Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents the parametric studies to obtain the optimum V-shaped angle plate due to blast load by using numerical simulations i.e., LS-DYNA. Constant magnitudes of mass of TNT and standoff distance were used while the angle of the V-shaped plate was varied in 5 °’ interval from 60 ° down to 10 °. This study found that the optimum V-shaped angle plate that could mitigate the maximum amount of blast load while experiencing minimal deformation at the vertex of the V-shaped plate was 25 °. Detailed parametric steps were presented in this study in order to arrive at the optimum angle of V-shaped plate to mitigate the blast load.